Analisis Pengelolaan Keuangan Desa di Pemerintah Kalurahan Banyuraden Kabupaten Sleman - Muhammad Fadhli Muzakki; Fajar Lisdiantara; Nurhaliza Puan Hapsari; Yogta Uswatun Khasanah (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2026)
This study aims to analyze the implementation of the Minister of Home Affairs Regulation Number 20 of 2018 in village financial management at Banyuraden Village, Gamping District. The study is motivated by the importance of transparent, accountable, effective, and regulation-compliant village financial management in supporting good village governance. A qualitative descriptive approach was employed. Data were collected through interviews with relevant stakeholders and analysis of various village financial management documents. The data were then analyzed using an interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that financial management in Banyuraden Village has been carried out in accordance with the provisions of Regulation Number 20 of 2018, covering the stages of planning, implementation, administration, reporting, and accountability. The application of transparency and accountability principles, along with the use of the Siskeudes application, has contributed to more orderly, systematic, and effective financial management.